Hubungan Pengembangan Karir Terhadap Sikap Profesional Perawat di Instalasi Rawat Inap Tulip/Kelas III RSUD Ulin Banjarmasin: The Relationship of Career Development to the Nurses Professional Attitude at Tulip Inpatient Installation/Class III RSUD Banjarmasin - Veronica Herliani; Mohammad Basit; Muhammad Sandi Suwardi (LPPM STIKES Guna Bangsa, 2023)
Background : Professional attitude is an attitude or behavior that is applied by a nurse in the profession when carrying out their duties based on the nursing ethics principles. With the nurses’ professional attitude it will have an impact on the given services quality. However thing that can be done to improve professional attitudes is career development. Objective : To find out the relationship of career development to the nurses’ professional attitude at Tulip Inpatient Installation/Class III RSUD Ulin Banjarmasin. Methods : This study uses quantitative methods and cross sectional study approach. The number of samples is 80 people with purposive sampling technique. The data were analyzed using the spearman rank test with a significant value of p<0.05. Result : The result of correlation test Spearman's rho with α = 0.05. From the result of the Spearman's rho statistical test obtained a significant value of 0.00 <0.05 indicated a relationship of career development to the nurses’ professional attitude with r = 0.479, which meant that the relationship of career development to the professional attitudes was in the medium category. Conclusion : There is a relationship of career development to the nurses’ professional attitude at Tulip inpatient installation/class III RSUD Ulin Banjarmasin. Keywords : Attitude, Career Development, Hospital, Nurse, Professional